Differential effects of cooling and humidification in urban green spaces and thresholds of vegetation community structure parameters: A case study of the Yangtze River Delta region - Sheng, Qianqian; Ji, Yaou; Jia, Chunyun; Jiang, Ling; Li, Chun; Huang, Zhengwei; Ma, Chunyan; Zhang, Xiangyi; Chen, Haonan; Wang, Tengyu; Zhu, Yifan; Zhu, Zunling (Cities, 2025)
The discomfort experienced by residents has increased due to the humid and hot conditions in urban environments. Urban green vegetation communities serve as effective means to regulate the urban microclimate and mitigate the urban heat island effect. However, the optimal threshold for the cooling and humidification effects, as well as the structural parameters of plant communities, remains unclear. This study focused on urban green spaces in the Yangtze River Delta region as the subject of research. Field surveys were conducted on 81 green spaces in mid-July 2023, during which basic information about the plant communities was documented. By utilizing instruments such as temperature and humidity meters, as well as laser rangefinders, the temperature and humidity data of various types of green vegetation communities were measured. This allowed for an analysis of the disparities in cooling and humidification effects among different types of green vegetation communities, and facilitated the quantification of the optimal threshold between these effects and the structural parameters of the community. The findings revealed that square green space and park green space exhibited superior cooling and humidification effects, whereas road green spaces and residential green spaces exhibited inferior effects. Additionally, arbor–grass and arbor–shrub–grass structured communities witnessed more favorable cooling and humidification effects, while arbor–shrub structured communities demonstrated the poorest effects. In terms of vegetation community growth types, the cooling and humidification effects ranked as follows from highest to lowest: coniferous and broadleaved mixed type > evergreen broadleaved type > evergreen and deciduous broadleaved mixed type > deciduous broadleaved type. Furthermore, a significant positive correlation was observed between the canopy closure of urban green vegetation communities and the cooling effect, although no significant correlation was found with the humidification effect. When the threshold of canopy closure fell between 0.72 and 0.88, the cooling effect was notably enhanced, and the cooling rate of green spaces remained above 3.8 %, with an optimal cooling effect observed at 0.74. Moreover, the study determined that both the ExtraTrees model and RF model effectively predicted the cooling effect of urban green spaces. Upon combining the research conclusions, three optimized patterns of plant community configuration were provided, thereby offering theoretical support for urban green space planning and plant application design. •First report on optimal cooling and humidifying thresholds in urban green spaces•Varying levels of cooling and humidifying effects in different types of urban green spaces•Positive impact of tree and herbaceous plant structures on cooling and humidifying effects.•Mixed needle-broadleaf and evergreen broadleaf communities have the best cooling and humidifying effects.•The study supports optimizing urban green space planning and vegetation use.